2013
DOI: 10.1186/1471-2105-14-s10-s7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of 2D diffusion processes based on microscopy data: parameter estimation and practical identifiability analysis

Abstract: BackgroundDiffusion is a key component of many biological processes such as chemotaxis, developmental differentiation and tissue morphogenesis. Since recently, the spatial gradients caused by diffusion can be assessed in-vitro and in-vivo using microscopy based imaging techniques. The resulting time-series of two dimensional, high-resolutions images in combination with mechanistic models enable the quantitative analysis of the underlying mechanisms. However, such a model-based analysis is still challenging due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…The estimation of model parameters from image data and identifiability analysis in the context of diffusion processes is an emerging area of research (29). We have reduced the Meinhardt model to a two-variable model, which is uniquely identifiable.…”
Section: Discussionmentioning
confidence: 99%
“…The estimation of model parameters from image data and identifiability analysis in the context of diffusion processes is an emerging area of research (29). We have reduced the Meinhardt model to a two-variable model, which is uniquely identifiable.…”
Section: Discussionmentioning
confidence: 99%
“…In this section we consider a PDE model describing the formation of gradients of the cytokine CCL21 around lymphatic vessels [17]. Such gradients are, among other processes, responsible for the migration of dendritic cells towards the lymphatic vessels.…”
Section: Example 2: Pde Model For Chemokine Gradient Formationmentioning
confidence: 99%
“…Of biological interest are the five unknown parameters: diffusion D, secretion α and degradation rate γ of CCL21 as well as the association k 1 and dissociation constant k −1 of the complex. For the detailed model, parameter inference and uncertainty analysis for those parameters we refer to the original publication [17]. In the original work the posterior probability was not calculate as it requires the simulation of the discretised PDE with several thousand state variables and is nearly infeasible with traditional methods.…”
Section: Example 2: Pde Model For Chemokine Gradient Formationmentioning
confidence: 99%
“…ABC determines probability distributions for the model parameters for each individual tissue explant (see Estimating parameters for our model in a deterministic manner appeared infeasible as preliminary studies suggested that our model had parameter structural non-identifiability, or functionally related model parameters [50]. While parameter identifiability has been explored extensively for ordinary differential equations, for example determining whether different parameter sets give rise to different model predictions, it has not been studied as deeply in partial differential equation models [51]. Thus, from preliminary analysis of parameter space and the knowledge that models similar to our own have shown non-identifiability relations between parameter values [52], we adopted ABC rejection because it allows for quantification of the uncertainty of our parameter estimates.…”
Section: Parameter Estimation Using Approximate Bayesian Computation mentioning
confidence: 99%